Bio-fortification of Agronomic Attributes and Biochemical Molecules in Black Night Shade as Influenced by Two Forms of Guinea Grass Biochar - Anthony Wale Ojewumi; Samuel Ayodotun Ayoola; Musa Hussaini Abdullahi; Zubedat Badru Adeola; Sunday Makinde Olubunmi (Zanco Journal of Pure and Applied Sciences, 2024)
This experiment was carried out in the greenhouse of Department of Botany, Lagos State University, Ojo, campus, South West, Nigeria in 2024. This study evaluated effects of guinea grass biochar (liquid and solid) on growth and nutritional profile in Black Night Shade (BNS). BNS seeds treated with 150% liquid biochar (LB) emerged 4days earlier, produced highest number of seedlings (8.44) and germination (84.38%) as well as plumule length (4.65 cm) in the seeds treated with 120% LB. Contribution (153.63%) and yield (27.41%) were substantially higher in the seeds treated with 150% LB. Plant height (42.33 cm) of the vegetable treated with 15g solid biochar (SB) as well as number of leaves (24.67) in the vegetable treated with 15g/L LB showed significant increase. In addition, Leaf area (51.91 cm²), Specific leaf area (167.81(m2 kg⁻1), leaf area index (0.13 m²/m2), and leaf area ratio (0.25(m2 kg‑1) were improved in BNS treated with15g/L LB .Relative growth rate (0.24(mgg‑1 day‑1) and net assimilation rate (0.08 (gm‑2 day‑1) showed similar significant increase in the vegetable treated with 15g SB. Dry matter fat, ash, crude fiber and carbohydrate were improved by15 g SB as well as most of the vitamins and minerals. In conclusion, 150% LB enhanced seedling emergence while 15g SB improved morphological traits and nutritional profile of BNS, therefore incorporation of the biochar at 15 g SB and 150% LB are suggested for production of BNS.